Do trabecular metal and cancellous titanium implants reduce the risk of late haematogenous infection? An experimental study in rabbits. Issue 6 (November 2021) - Komnos, George; Banios, Konstantinos; Kolonia, Konstantina; Poultsides, Lazaros A; Petinaki, Efthimia; Sarrou, Styliani; Zintzaras, Elias; Karachalios, Theofilos
Aim: This study evaluated the late resistance to haematogenous contamination by microbial pathogens of implants and bone-implant interface and the development of late clinical infection when cementless components with different surface or structural properties are implanted. Material and methods: 50 adult male New Zealand white rabbits were divided into 5 groups of 10 animals each. In Group A smooth titanium, in Group B grit blasted titanium, in Group C HA-coated titanium, in Group D trabecular metal and in group E cancellous titanium rods were implanted in the right proximal tibia. Four weeks later, 1 ml of inoculum of a standardised CA-MRSA strain (3 × 10 8 cfu/ml) was injected through a femoral artery catheter (groups B, C, D, E) while in group A, 1 ml of sterile saline was injected in a similar way (control group). Subjects were killed 8 weeks after the initial procedure and 3 samples of each tibial specimen were subjected to conventional cultures and PCR studies. Results: The number of the specimens (conventional cultures and PCR studies) contaminated by the standardized pathogen was as follows: Group A: 0/10, Group B: 7/10, Group C: 6/10, Group D; 5/10 and Group E: 5/10. Comparing the number of colony form units isolated from the implant samples, Group B (GB titanium) showed statistically significantly higher values (Mann-Whitney test) compared to Group C ( p  = 0.044), Group D ( p  = 0.040) and Group E ( p  = 0.038). Local active infection was observed in 6 animals: 3 in Group B; 1 in Group C, 1 in Group D, and 1 in Group E. Conclusions: Modern cementless implants (trabecular metal and cancellous titanium) showed a lower risk of implant contamination and late clinical haematogenous infection.